Double-bundle and double-tunnel ACL reconstruction with looped proximal tibial fixation (2011)
Double-bundle anterior cruciate ligament (ACL) reconstruction can be demanding and time consuming and requires twice as many implants, increasing both costs and possible complications. In this article, we present a new approach to double bundle ACL reconstruction: a biological fixation of the tibial side by means of a double tunnel and a U-shape passage of an anterior tibialis allograft, fixed into a double tunnel on the femoral condyle with 2 interference bioabsorbable screws. The technique is designed to combine 2 known procedures for the regular knee surgeon: the mono-tunnel technique and the medial-portal approach.